2020
DOI: 10.28932/jmm.v19i2.2425
|View full text |Cite
|
Sign up to set email alerts
|

Analisis work engagement karyawan frontline high-contact dan low-contact di industri jasa

Abstract: Work engagement (positive working mind and emotion) in frontline employees (FLEs) plays an important role that will affect the capability of the organization in serving its customer. The goal of this research is to examine whether there were differences in the influence of service climate, job satisfaction, and affective commitment toward work engagement in high-contact and low-contact frontline employees in Jakarta and Tangerang; and whether there were influences of work engagement toward adaptability behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…So, if the level of affective commitment of employees is high, it will have a good impact on empl oyee work engagement. The result is similar to the research of Yusnita & Megawati (2018); Asan & Huliselan (2020); Koroh et al (2021) that affective commitment has a positive effect on work engagement. Based on the results of hypothesis testing, H3 is accepted and shows that affective commitment has a positive and significant effect on knowledge sharing.…”
Section: Inner Model Evaluationsupporting
confidence: 90%
See 1 more Smart Citation
“…So, if the level of affective commitment of employees is high, it will have a good impact on empl oyee work engagement. The result is similar to the research of Yusnita & Megawati (2018); Asan & Huliselan (2020); Koroh et al (2021) that affective commitment has a positive effect on work engagement. Based on the results of hypothesis testing, H3 is accepted and shows that affective commitment has a positive and significant effect on knowledge sharing.…”
Section: Inner Model Evaluationsupporting
confidence: 90%
“…Work engagement is also described as the extent to which individuals pay attention to and explore their role in the organization, resulting in a positive attitude and outlook (Koroh et al 2021). Factors affecting work engagement include work demands arising from work demands (Asan & Huliselan, 2020). Work engagement's dimensions are based on Schaufeli et al's theory, including vigor, dedication, and absorption (Bakker & Albrecht, 2018).…”
Section: Work Engagementmentioning
confidence: 99%
“…This research indicated that affective commitment directly has a significant impact on work involvement. This is similar to research conducted by Asan & Huliselan (2020) who examined frontline employees and Koroh et al ( 2021) who examined employees in Kupang City. The results indicated that affective commitment has a positive effect on work involvement.…”
Section: Introductionsupporting
confidence: 88%
“…Kahn (1990), found that sympathetic and trusting interpersonal relationships, as well as a supportive intra-teamwork, promote employee engagement. Supportive intra-teamwork environments allow members to experiment and to try new things and even fail without fear of the consequences (Kahn, 1990), to be more engaged and productive in a workplace (May et al, 2004;Asan and Huliselan, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 99%